Parents’ perceptions of sleep problems in children with ADHD when using weighted blankets - Lönn, Maria; Erlandsson, Lena Karin; Aili, Katarina; Svedberg, Petra; Jarbin, Håkan; Larsson, Ingrid (Scandinavian Journal of Occupational Therapy, 2025)
Background: Parents’ perceptions of children’s sleep problems when using a weighted blanket could enhance the understanding of challenges faced by families with ADHD and sleep problems. This is in alignment with a client-centred approach. Acknowledging, what parents perceive as a problem in a family context. Aim: To explore changes in parents’ perceptions of their children’s sleep problems before and after participation in a sleep intervention with weighted blankets. Methods: Children with ADHD (n = 45) aged 6–14 participated in a sleep intervention with weighted blankets. Data-collection (baseline + 16-week) using the Children’s Sleep Habits Questionnaire. Results: Common sleep problems, such as bedtime resistance, daytime sleepiness, sleep onset delay, and sleep duration, were reported to have improved in 50–75% of the children after using a weighted blanket, according to their parents. Changes were seen also for the less commonly reported parasomnias and nightly awakenings, and these problems were rarely perceived as persistent. Conclusions: Reported improvements covered various sleep domains, though some sleep issues persisted. Future evaluation of the effects of weighted blanket should assess multiple dimensions of sleep, before and after use. Significance: The client-centred approach, including parents’ perceptions of children’s sleep problems, is important in the evaluation of weighted blankets for children with ADHD.
Keywords: Assistive technology; client-centred practice; emotional regulation; occupational therapy, sleep disorders